Acne Supplements Sold Online - Emily Burns; Milbrey Parke; Ariadna Perez-Sanchez; Dina Zamil; Rajani Katta (Mattioli1885, 2022)
Introduction: As no centralized database of acne supplements is available, we aimed to provide an overview of these products, with a focus on safety. Objectives: The objectives of this study were to document the number, formulation, contents, and marketing strategies utilized by acne supplements sold online. Methods: An online search was conducted between March and May 2020. Products were included in the study if they used the terms: "whitehead", "blackhead", or "acne". Data were extracted from the website, box, and Supplement Facts label. Results: 49 products were identified, which contained 146 unique ingredients. These included vitamins, minerals, food extracts, botanical extracts, amino acids, animal products, and distinct microbial strains. Few (4.1%) products were tested by third parties. Conclusions: This survey of acne supplements available online raised concerns regarding lack of warning labels, teratogenicity, exceedingly large levels of vitamins and minerals, and lack of third-party testing. Given the limited regulation and oversight of dietary supplements, it is imperative that physicians educate patients on the potential risks of these products.